2020
DOI: 10.3389/fimmu.2020.01210
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Chemical Variety of Small-Molecule-Based TLR4 Modulators: An Overview

Abstract: Toll-Like Receptor 4 (TLR4) is one of the receptors of innate immunity. It is activated by Pathogen- and Damage-Associated Molecular Patterns (PAMPs and DAMPs) and triggers pro-inflammatory responses that belong to the repertoire of innate immune responses, consequently protecting against infectious challenges and boosting adaptive immunity. Mild TLR4 stimulation by non-toxic molecules resembling its natural agonist (lipid A) provided efficient vaccine adjuvants. The non-toxic TLR4 agonist monophosphoryl lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 113 publications
0
34
0
Order By: Relevance
“…LPS as a prominent PAMP is a potent endotoxin that is sensed by the PRR receptor toll-like receptor (TLR) 4 [63,64]. Earlier studies reported that extremely low LPS doses (femtomolar) may trigger the activation of myeloid differentiation factor-2 (MD-2)/TLR4 complex, most probably due to the increased sensitivity driven by CD14 [65][66][67][68]. Activation of TLR4 results in a cascade of signaling events promoting the release of inflammatory mediators mainly by a concordant activation of NFκB, especially p65 [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…LPS as a prominent PAMP is a potent endotoxin that is sensed by the PRR receptor toll-like receptor (TLR) 4 [63,64]. Earlier studies reported that extremely low LPS doses (femtomolar) may trigger the activation of myeloid differentiation factor-2 (MD-2)/TLR4 complex, most probably due to the increased sensitivity driven by CD14 [65][66][67][68]. Activation of TLR4 results in a cascade of signaling events promoting the release of inflammatory mediators mainly by a concordant activation of NFκB, especially p65 [69,70].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is worth noting that while MPLA disaccharide is an important scaffold for the phosphate and acyl group, it is not strictly required for eliciting TLR4 signaling. Structural analogues of MPLA in which the sugar backbone is substituted by other chemical groups that can provide scaffold function retain immunological properties ( Romerio and Peri, 2020 ).…”
Section: Carbohydrates As Vaccine Adjuvantsmentioning
confidence: 99%
“…Some molecules like MPLA are key components of adjuvant formulations that are part of licensed vaccine ( O’Hagan et al., 2020 ). However, the sugar component functions mainly as scaffold for the acyl chains which is key to trigger TLR4-mediated signaling ( Cochet and Peri, 2017 ; Romerio and Peri, 2020 ). Several molecules that have shown adjuvant activity in pre-clinical and in some cases clinical studies, such as α-GalCer and TDB, are glycolipids and therefore structure-activity relationship studies will be key to define the relative contribution of sugar and lipid moieties to adjuvant activity ( Pifferi et al., 2021 ).…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…A large amount of experimental data shows that LPS can cause systemic inflammatory response syndrome (SIRS) ( 1 , 2 ). It is an endotoxin that can not only be secreted in the form of outer membrane vesicles (OMVs) but can also be released by forming micelles in the bacterial membrane ( 3 ). LPS is transported to the cytoplasm of immune cells in the form of OMVs, and inflammatory caspases, as the specific receptors of LPS, can activate the production of downstream pro-inflammatory factors ( 4 ).…”
Section: Introductionmentioning
confidence: 99%